Penerapan Laporan Keuangan Berdasarkan SAK EMKM Bagi Usaha Mikro Kecil Menengah di Kecamatan Gebang - Sakdiah, Khairani; Pohan, Anjur; Sinaga, Asmawarna (Pusdikra Publishing, 2023)
Each region typically boasts its distinctive flagship products within the realm of SMEs, and this holds true for the Gebang sub-district of Langkat Regency, where roadside businesses thrive with their specialty products like